Pengaruh Lingkungan Pendidian Islami terhadap Karakter Anak Usia Sekolah - Maemunah, Yayah; Wahyudi, Undang Ruslan (ANWARUL, 2022)
Many factors can influence student learning success, one of which is theeducational environment at school. A good and comfortable school education environment and conducive to student learning will produce good student output, both in terms of cognitive, psychomotor, and affective (character).This study aims to prove that the Islamic educational environment greatly influences the character of school-age students. In this study the authors took data from 4 parents of students as a sample, who sent their sons to the Integrated Islamic School (SIT) and to the boarding school. This study uses the case study method, by collecting data from interviews with parents who send their sons to SIT and boarding schools. The results of the study show that the influence of the Islamic education environment applied at SIT and boarding schools greatly influences children's character. Children become diligent in praying, more polite, more refined in speaking, more independent, more fluent in reading the Qur'an, and many other good characters. This is in accordance with the ecological theory of Uri Bronfenbrenner, a psychologist from Cornell University in the United States, which states that human development is influenced by the environmental context. This ecological theory is in accordance with the hadith of the Prophet SAW which states that every child is born in a state of fitrah, then both parents will make the child a Jew, Christian or Magi.